ABSORÇÃO DE NUTRIENTE EM CULTIVARES DE AVEIA SUBMETIDAS AO ESTRESSE POR ALUMÍNIO - VALENTINI, ANA P. F.; ZAMBONATO, FELIPE; CARVALHO, FERNANDO; GAVIRAGHI, FERNANDO; MARTINS, JOÃO A. K.; SILVA, JOSE A. G. D.; WAGNER, JULIANO F.; UHDE, LEONIR; CRESTANI, MARAÍSA; FERNANDES, SANDRA B. V. (Salão do Conhecimento, 2013)
Resumo